(untitled) (European Journal of Interdisciplinary Research and Development, 2026)
This article is devoted to the study of the influence of socio-cultural factors on the formation and evolution of the axiological conceptosphere and the transformation of the axiological lexicon. It highlights the dynamic nature of value systems and their dependence on historical, cultural, and social changes. The paper examines how shifts in society—such as globalization, technological progress, and changes in ideological paradigms—affect the structure of values and their linguistic representation.